Ecolalia e metáfora: um estudo apoiado na teoria da enunciação de Émile Benveniste. - Souza, Ana Fabrícia Rodrigues de (2018)
This work intends to discuss the metaphor relating it to the echolalia, bringing some perspectives on the subject in the enunciative field, that considers the subjectivity of the speech putting the subject in the center of the discussions.We analyzed echolalia, as a language disorder, associating it with the concept of metaphorical language under the scope of Émile Benveniste's Theory of Enunciation (1991, 2006). It was chosen to perform a qualitative research of an applied nature with the explanatory objective, following the bibliographic procedure, because it was deemed necessary to investigate the echolalia of a place other than a decontextualized repetition of the speech of another. For this, the subject in question was related to the metaphor, because it is similar in the fact that both represent a possible analogical transposition in the discourse. After analyzing the concept of metaphor under the classical, structuralist, functionalist, cognitive and enunciative aspects, confronting them with the notion of echolalia within the linguistic field, phonoaudiological and psychoanalytic, bringing to the discussion examples illustrative of echolonic language taken from specialized scientific publications, that one can perceive that it is in the analogy that is made within the discourse of the speaker, in the process of resignification that marks its singularity, that the acting subject is seen. In this comment, we undertake that the echolalia speech assumes the role not only of an empty speech, or disembodied speech, but of a metaphorical language from the enunciative point of view. The results found, through the analysis in cases of Autism and one Alzheimer's case, corroborate a new perception of echolalia, which is no longer seen as an "empty" speech, but as a single speech mark that re-means, that is, presents a sense within a context.